Hubungan waktu tunggu pelayanan resep racikan pasien bpjs terhadap tingkat kepuasan pasien di farmasi rawat jalan di Rumah Sakit ‘x’ Kota Malang - Siwi , Mayang Aditya Ayuning; Sari , Puspita Maya; Aprilianti , Rakhmadani Gadis (Journal of Pharmaceutical and Sciences, 2025)
One of the minimum standards of hospital pharmacy services is waiting time. Waiting time is one of the potential components that can affect the level of patient satisfaction and also the quality of the hospital. Another indicator of the success of health services is patient satisfaction. Patient satisfaction is a reflection of the quality of health services they receive. The purpose of this study was to determine the relationship between waiting time for BPJS patient prescription services and the level of patient satisfaction at the outpatient pharmacy of Hospital 'X' in Malang City. This study design is quantitative descriptive with a Cross Sectional approach. The data collection method is Prospective, sampling using Random Sampling techniques during the period December 2023 - January 2024. The data analysis used is bivariate analysis of the Chi Square test to see the relationship between waiting time and patient satisfaction. The number of samples taken was 84 respondents. The results showed that the waiting time for compounded prescription services at the outpatient pharmacy of Hospital 'X' in Malang City was obtained as much as (51.2%) not according to standards with an average time of 81.25 minutes. The level of patient satisfaction as many as (46.4%) felt satisfied with the service at the outpatient pharmacy of Hospital 'X' in Malang City and the p-value was 0.04 (˂ 0.05). Based on the results of this study, it can be concluded that the waiting time for BPJS compounded prescription services is related to the level of patient satisfaction at Hospital 'X' in Malang City.